1990
DOI: 10.1021/jm00163a006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of cholesterol biosynthesis. 2. 1,3,5-Trisubstituted [2-(tetrahydro-4-hydroxy-2-oxopyran-6-yl)ethyl]pyrazoles

Abstract: A series of 1,3,5-trisubstituted pyrazole mevalonolactones were prepared and evaluated for their ability to inhibit the enzyme HMG-CoA reductase in vitro. Since previous studies suggested that the 5-(4-fluorophenyl) and 3-(1-methylethyl) substituents afforded optimum potency, attention was focused on variations in position 1 of the pyrazole ring. Biological evaluation of analogues bearing a variety of 1-substituents suggested that, although most substituents were tolerated, none afforded an advantage over phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These structures represent indispensable components of the modern medicinal chemistry repertoire 2. Pyrazoles, while rarely found in nature, serve as important core structures of many pharmaceuticals and pharmaceutical leads with a wide range of biological activities (e.g., cholesterol lowering,3 anti-inflammatory,4 anti-cancer,5 anti-depressant and anti-psychotic agents6). As a result, there is a continuing interest in the development of versatile methods to access highly substituted pyrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…These structures represent indispensable components of the modern medicinal chemistry repertoire 2. Pyrazoles, while rarely found in nature, serve as important core structures of many pharmaceuticals and pharmaceutical leads with a wide range of biological activities (e.g., cholesterol lowering,3 anti-inflammatory,4 anti-cancer,5 anti-depressant and anti-psychotic agents6). As a result, there is a continuing interest in the development of versatile methods to access highly substituted pyrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…These reports were followed up by scientists at the then Parke-Davis division of Warner-Lambert, well before the takeover by Pfizer, demonstrating that the same 'natural product warhead' as in mevinolin, coupled to either fluorophenyl-substituted pyrroles [51] or 1,3,5-trisubstituted triazoles [52], were also active entities, basically comparable to compactin, although reference to the patent literature shows that a Sandoz scientist had filed a US patent in 1985 (issued in 1986) [101] covering the pyrazole nucleus. Contemporaneously, Rosen and Heathcock published an excellent review covering the synthesis of mevinic acids that also showed some of the early 'synthetic derivatives of mevinolin' [53].…”
Section: Anticholesterolemicsmentioning
confidence: 99%
“…For these experiments, we used PD123588, a compound that is structurally dissimilar to lovastatin ( Fig. 2) and is slightly less active than both lovastatin and simvastatin in its effectiveness of inhibiting HMG-R in vitro (Alberts et al, 1980;Endo, 1980;Sliskovic et al, 1990;Endo, 1992). As was the case for lovastatin, PD123588 acted to block clam oocyte activation ( Fig.…”
Section: Inhibitors Of Hmg-coa Reductase Activity Block Activation Ofmentioning
confidence: 99%
“…Two types of HMG-R inhibitors mainly are used in this study, lovastatin and PD123588. Both lovastatin, which is isolated as a fungal metabolite (Alberts et al, 1980;Endo, 1980) and PD123588, which is synthetically derived (compound 10 in [Sliskovic et al, 1990]), were developed independently for use as drugs effective in lowering plasma cholesterol in hypercholesterolemic patients. They act to inhibit HMG-R, a microsomal enzyme that catalyzes the reduction of HMG-CoA to mevalonate, which is the ratelimiting step in the synthesis of cholesterol (Goldstein and Brown, 1977).…”
Section: Mechanisms Of Action For Hmg-r Inhibitorsmentioning
confidence: 99%